Obesity and its relation with diabetes and hypertension: a cross-sectional study across four low- and middle-income country regions - Patel, Shivani A. (Glob Heart, 2016)
BACKGROUND: The implications of rising obesity for cardiovascular health in low- and middle-income countries (LMICs) has generated much interest, in part because associations between obesity and cardiovascular health appear to vary across ethnic groups. OBJECTIVE: We assessed general and central obesity in four regions—Africa, East Asia, South America, and South Asia. We further investigate whether 1) body mass index (BMI) and waist circumference differentially relate to cardiovascular health; and 2) associations between obesity metrics and adverse cardiovascular health vary by region. METHODS: Using baseline anthropometric data collected between 2008 and 2012 from 7 cohorts in 9 countries, we estimated the proportion of participants with general and central obesity using BMI and waist circumference classifications, respectively, by study site. We used Poisson regression to examine the associations (prevalence ratios) of continuously measured BMI and waist circumference with prevalent diabetes and hypertension by sex. Pooled estimates across studies were computed by sex and age. RESULTS: 31,118 participants aged 20 to 79 years were analyzed. General obesity was highest in South Asian cities and central obesity was highest in South America. The proportion classified with general obesity (range 11% to 50%) tended to be lower than the proportion classified as centrally obese (range 19% to 79%). Every standard deviation higher of BMI was associated with 1.65 and 1.60 times higher probability of diabetes and 1.42 and 1.28 times higher probability of hypertension, for men and women respectively, aged 40–69 years. Every standard deviation higher of waist circumference was associated with 1.48 and 1.74 times higher probability of diabetes and 1.34 and 1.31 times higher probability of hypertension, for men and women respectively, aged 40–69 years. Associations of obesity measures with diabetes were strongest in South Africa among men and in South America among women. Associations with hypertension were weakest in South Africa among both men and women. CONCLUSIONS: BMI and waist circumference were both reasonable predictors of prevalent diabetes and hypertension. Across diverse ethnicities and settings, BMI and waist circumference remain salient metrics of obesity that can identify those with increased cardiovascular risk.